2018
DOI: 10.1159/000487578
|View full text |Cite
|
Sign up to set email alerts
|

Voruciclib, a Potent CDK4/6 Inhibitor, Antagonizes ABCB1 and ABCG2-Mediated Multi-Drug Resistance in Cancer Cells

Abstract: Background/Aims: The overexpression of ATP-Binding Cassette (ABC) transporters has known to be one of the major obstacles impeding the success of chemotherapy in drug resistant cancers. In this study, we evaluated voruciclib, a CDK 4/6 inhibitor, for its chemo-sensitizing activity in ABCB1- and ABCG2- overexpressing cells. Methods: Cytotoxicity and reversal effect of voruciclib was determined by MTT assay. The intracellular accumulation and efflux of ABCB1 and ABCG2 substrates were measured by scintillation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The results of the accumulation and efflux experiments were congruent with the reversal effects of VS-4718 shown in anti-cancer efficacy testing when co-administered with substrate-drugs, suggesting that VS-4718 may increase the accumulation of substrate-drugs in ABCB1- and ABCG2-overexpressing cancer cells by inhibiting the ABCB1- and ABCG2-mediated efflux activity, which led to the decline of IC 50 of substrate-drugs and finally attenuated the ABC transporter-mediated MDR. The results are also consistent with studies of our other small-molecule reversal reagents (Zhang et al, 2017 , 2018 ; Gupta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the accumulation and efflux experiments were congruent with the reversal effects of VS-4718 shown in anti-cancer efficacy testing when co-administered with substrate-drugs, suggesting that VS-4718 may increase the accumulation of substrate-drugs in ABCB1- and ABCG2-overexpressing cancer cells by inhibiting the ABCB1- and ABCG2-mediated efflux activity, which led to the decline of IC 50 of substrate-drugs and finally attenuated the ABC transporter-mediated MDR. The results are also consistent with studies of our other small-molecule reversal reagents (Zhang et al, 2017 , 2018 ; Gupta et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…CC-671 obtained a docking score of −12.318 kcal/mol. Furthermore, the docking score of CC-671 is comparable to other reported ABCG2 reversal agents such as selonsertib (−11.094 kcal/mol), 56 voruciclib (−10.304 kcal/mol), 57 and ZM323881 (−11.509 kcal/mol). 58 Of note, the molecular docking is not meant to be an accurate affinity predictor, thereby the bound conformation might not represent the actual binding situation 59 and is therefore used as a reference in this study.…”
Section: Cc-671 Showed High Binding Affinity With Abcg2 In Moleculasupporting
confidence: 66%
“…It has been reported that the ATPase activity of P-gp was increased by voruciclib at low to moderate concentrations (not exceeding 7 μM) but was inhibited by CCT129202 [58], although both compounds were categorized as inhibitors/substrates [24]. Together with a recent report indicating that ATP binding to P-gp, but not inducing hydrolysis, promotes release of the substrate [26], these findings indicate that the variance in ATPase activity showing hydrolysis by ABC transporters may be a response to a ligand binding to ABC transporters but does not necessarily indicate inhibition or activation by this ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The ATPase activity of P-gp and BCRP in crude membranes of High-Five insect cells was measured in the presence of BAY-1082439 (0 to 40 μM) by PREDEASY ATPase Kits with modified protocols, as previously described [23,24].…”
Section: Atpase Activity Assaymentioning
confidence: 99%